2012
DOI: 10.1108/17542731211191221
|View full text |Cite
|
Sign up to set email alerts
|

Approach for measuring health‐related quality management

Abstract: Purpose -The purpose of this paper is to develop an approach to measuring health-related quality management based on earlier research on the connection between quality management and employee health. Design/methodology/approach -A questionnaire was developed and a research study was carried out at a manufacturing company. The constructs were tested for internal reliability using Cronbach's alpha tests. The dimensions' correlations with employee health were checked using Pearson correlation. Findings -Three of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6

Relationship

6
0

Authors

Journals

citations
Cited by 19 publications
(48 citation statements)
references
References 26 publications
1
47
0
Order By: Relevance
“…There is also research which describe how Quality Management can be practiced to support sustainable health among co-workers and also what is of most importance within Quality Management to influence coworkers' sustainable health (Bäckström, 2009, Lagrosen et, al, 2010. The results show that the value ‗Leadership Commitment' and the value ‗Participation of Everybody' are important to support sustainable health among co-workers when Quality Management is practiced (Bäckström, 2009, Lagrosen et al, 2011 The underlying dimension of the values ‗Leadership Commitment' and ‗Participation of Everybody' regarding the relation to co-worker health was examined by Lagrosen and Bäckström (2005) and Lagrosen et al, (2010). In that study, it was pointed out that integrity, presence and communication, empathy and continuity are underlying dimensions of ‗Leadership Commitment'.…”
Section: Health Promotion and Measuring Health-related Quality Managementioning
confidence: 99%
See 2 more Smart Citations
“…There is also research which describe how Quality Management can be practiced to support sustainable health among co-workers and also what is of most importance within Quality Management to influence coworkers' sustainable health (Bäckström, 2009, Lagrosen et, al, 2010. The results show that the value ‗Leadership Commitment' and the value ‗Participation of Everybody' are important to support sustainable health among co-workers when Quality Management is practiced (Bäckström, 2009, Lagrosen et al, 2011 The underlying dimension of the values ‗Leadership Commitment' and ‗Participation of Everybody' regarding the relation to co-worker health was examined by Lagrosen and Bäckström (2005) and Lagrosen et al, (2010). In that study, it was pointed out that integrity, presence and communication, empathy and continuity are underlying dimensions of ‗Leadership Commitment'.…”
Section: Health Promotion and Measuring Health-related Quality Managementioning
confidence: 99%
“…Correlations between co-workers' perceptions of their health and values within Quality Management have also been found (Lagrosen, 2004;Lagrosen et al, 2007). A well-developed, structured approach for health-related quality management can be used as a management tool in order to assess and improve employees' well-being, satisfaction and motivation (Lagrosen et al, 2011). Taken all in all, research, knowledge and support to the management within the health promotion area are important.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A questionnaire measuring co-workers' perceived health has been developed and tested by Lagrosen, Bäckström and Wiklund (2012). This questionnaire has been used in several research projects with different purposes to measure co-workers' perceived health, see for instance Bäckström, Eriksson and Lagrosen (2012a) ;Bäckström et.…”
Section: Methodsmentioning
confidence: 99%
“…Earlier research has shown that the value 'Leadership Commitment' and the value 'Participation of Everybody' are important to support sustainable health among co-workers when Quality Management is practiced (Bäckström, 2009;Lagrosen, Bäckström and Wiklund, 2012). The underlying dimension of the 'Leadership Commitment' value regarding the relation to co-worker health was examined by Lagrosen and Bäckström (2005) and Lagrosen, Bäckström and Lagrosen (2010).…”
Section: Co-worker Health and Leanmentioning
confidence: 99%